Finite element simulation of rotary swaging process of tube-shaped workpieces / Renganathan Sekar ...[et al.] - Sekar, Renganathan; Razali, Mohd Kaswandee; Man, Soo Joun (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The applications of tube-shaped workpieces have been growing steadily across many industries, thanks to its advantages like lightweight and versatility in assembly. This increase in demand must be met with efficient near net shape manufacturing processes like rotary swaging which is also gaining industrial prominence in the recent years. The process investigated in this paper is a category of recess type swaging process with mandrel where there is no axial movement of the workpiece. Initially, the FE methodology is validated by comparing the predictions of a similar process with the experiments. Using the same methodology and FE tools, a FE model is created for the rotary swaging process with six dies. The nodal velocity, effective strain and effective stress distribution from the simulation were investigated and a good agreement was found between the theory and predictions. The intelligent metal forming simulator AFDEX is used for carrying out the finite element analysis. The axial velocity is found to be maximum in the sizing zone during the deformation process and the tubeshaped workpiece experiences triaxial stress states. This simulation framework can be used for quicker development and optimization of process design for tube shaped workpieces.